Social dynamics of Japanese immigrants in Aru islands from late 19th century to early 20th century - Pangastoeti, Sri (Japanese Research on Linguistics, Literature, and Culture, 2022)
From late 19th century to early 20th century, Aru Islands, Maluku had been a region frequented by Japanese immigrants. Their presence differed to the presence of Japanese immigrants in other parts of Indonesia during the same time period. Pearls of high quality were an exquisite treasure found in the waters of Aru, which attracted Japanese immigrants to come to the region. The present study attempts to investigate their arrival and how they had lived their life in a region that is geographically and culturally different from that of Japan. By using sources obtained from Japan, the Netherlands, and Indonesia, the current study found that there were conflicts and harmony observed within the social life dynamics of Japanese immigrants living in Aru Islands. Both were found to have occurred internally within the Japanese immigrant community and in their relations with other communities in Aru. One of the factors that had a significant influence on their social relations was the ethnic and social classes that were developed by the course of history.---Pada akhir abad ke-19 sampai awal abad ke-20 Kepulauan Aru, Maluku merupakan sebuah wilayah yang banyak didatangi oleh imigran Jepang. Keberadaan mereka berbeda dengan keberadaan imigran Jepang di wilayah lain di Indonesia pada masa yang sama. Mutiara yang berkualitas yang menjadi kekayaan perairan Aru memang menjadi daya tarik kedatangan imigran Jepang. Kajian ini akan menelusuri kedatangan mereka, dan bagaimana mereka menjalani kehidupan d wilayah yang secara geografis dan kultur sangat berbeda dengan Jepang. Dengan menggunakan sumber dari Jepang, Belanda, dan Indonesia , kajian ini menemukan bahwa dalan dinamika kehidupan sosial imigran Jepang di Kepulauan Aru, ada harmoni dan konflik. Keduanya terjadi baik di dalam komunitas imigran Jepang sendiri, maupun dalam relasi mereka dengan komunitas lain di Aru. Salah satu faktor yang cukup berpengaruh dalan relasi sosial mereka adalah kelas sosial dan etnisitas yang dibentuk oleh perjalanan sejarah.